Investigation of Mechanical and Tribological Properties of AA6061/MWCNT/B4C Hybrid Metal Matrix Composite. (30th September 2022) - Satishkumar, P.; Natarajan, N.; Saminathan, Rajasekaran; Hillary, J. Justin Maria; Birhanu, Biru; Alguno, Arnold C.; Capangpangan, Rey Y.; Raj, Vishnu; Livingston, Stephen
Abstract : Carbon nanotubes (CNTs) and graphene, in particular, have been the subject of many recent studies since their discovery in the early 2000s. Because of their unusual properties, carbon nanotubes (CNTs) have piqued the interest of scientists across a wide range of disciplines. An Al matrix was reinforced with powder metallurgy-fabricated B 4 C and CNT composites. The nanocomposite aluminium matrix was examined for tribological behaviour, density, stiffness, and compressive strength before and after hot isostatic pressing (HIP). Scanning electron microscopy and TEM were used to analyze the carbon nanotubes and their hybrid counterparts (SEM). The density of nanocomposites was reduced by 38% without HIP but by 45% after it was added to the mixture. Hardness was also increased by 40%, but following HIP, the hardness rose to 67%. Before and after HIP, the compression strength increased by 39% and 60%, respectively. HIP improves the wear rate by 45%, and B 4 C and CNTs improve the coefficient of friction by 20% in all volume fractions but only by 48% in the case of nanocomposites.